2020
DOI: 10.1371/journal.pone.0244435
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tree age, daily sap volume and date of sap collection on the content of minerals and heavy metals in silver birch (Betula pendula Roth) tree sap

Abstract: The aim of this study was to determine the effect of the age of trees, daily sap volume as well as the term of tapping birch sap collected in the forest environment on the content of selected minerals (zinc, copper and manganese) and heavy metals (lead, nickel, chromium and cadmium). The study was performed on material taken from two stands (aged 34 and 84 years) in a moist broadleaved forest habitat with a dominant share of silver birch (Betula pendula Roth). The research results confirmed the presence of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This makes it possible to use birch as a monitoring plant and focus on the leaves as the largest accumulators, as the authors emphasise, of zinc and sometimes cadmium. Hence, most research on birch focuses on the issue of the content of heavy metals in leaves or in the roots [ 8 , 10 , 16 , 17 , 62 , 64 – 72 ], and increasingly also sap [ 29 , 73 – 76 ]. It is worth paying attention to the other uses of birch.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to use birch as a monitoring plant and focus on the leaves as the largest accumulators, as the authors emphasise, of zinc and sometimes cadmium. Hence, most research on birch focuses on the issue of the content of heavy metals in leaves or in the roots [ 8 , 10 , 16 , 17 , 62 , 64 – 72 ], and increasingly also sap [ 29 , 73 – 76 ]. It is worth paying attention to the other uses of birch.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic microorganisms E. coli and Salmonella were not detected in the thawed sap at various depths, while molds were found in amounts of <1 log CFU/mL. Birch sap is an ideal medium for microorganisms because it contains enough available organic compounds and mineral substances, so the sap ferments rather quickly [10,20]. It was determined that in the upper part of the container (where the depth of the thawed sap was 10-30% the depth of the sap in the container) the total amount of microorganisms was even lower than that in fresh birch sap, at 1.27 log colony-forming units (CFU) per milliliter and 1.60 log CFU/mL, respectively.…”
Section: Composition and Physicochemical Indicators Of Thawed Sap At ...mentioning
confidence: 99%
“…Harvesting and processing birch sap is a delicate and precise procedure that requires a careful understanding of the birch tree's biology and the optimal time to tap into its sap. Researchers have found that the chemical composition of birch sap depends on the type of birch habitat [8,9], the age of the birch tree, the daily sap volume, and the date of sap collection [10]. Typically, sap is harvested in early spring when the sap begins to rise and before the buds open.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Cr is not only recorded in food crops but also in forest trees. The health of forest plants has been at risk because of exacerbated Cr content in the soil [ 37 ]. Globally, there have been reports on the effects of increased Cu, Fe, Mn, Mo, Zn, Ni, and other PTEs on soils, plants, animals, humans, and water.…”
Section: Introductionmentioning
confidence: 99%